Iron kissed - Briggs, Patricia (Briggs, Patricia. Mercy Thompson novels., 2012)
Shapeshifting mechanic Mercy Thompson finds her loyalty sorely tested when her former boss and mentor is arrested for murder and left to rot behind bars by his own kind, while she is trying to choose between Sam and Adam, the two werewolves she loves.